(untitled) (Revista Latino-Americana de Enfermagem, 2024)
Objective: to analyze the use of quality assessment indicators and their implementation to improve quality in the processing of health products. Method: a mixed-methods study with a multiple case approach using Structure, Process and Results indicators and elaboration of a plan using Appreciative Inquiry, carried out in four central sterile supply departments from hospital units. Results: the indicators for the Cleaning stage presented 47.8% compliance for Structure and 59.0% for Process: in addition 71.8% of the products were clean. In the Preparation operational stage, 50.0% of the Results indicators were in compliance for Structure and 66.7% for Process. In the Sterilization, Storage and Distribution stage, 43.5% compliance was obtained for Structure, 55.7% for Process and 78.6% for Packaging conservation. Appreciative planning proposed improvements to the physical structure, review of processes and protocols, promotion and appreciation of the work done and strengthening of teaching about processing and service management, highlighting the protagonism of the group and of the leaders. Conclusion: using indicators was positive in materializing reality; however, it was verified that the improvements proposed are related to people. The affirmative and constructive view of Appreciative Inquiry presented itself as a path to changes and quality improvements.